DESIGN VISUAL COMPONENT SLIDES FOR TEACHING COMPUTER PRESENTATIONS (Journal of Information Technologies in Education (ITE), 2013)
The article analyzes the common mistakes that allow educators and teachers in the design of the visual component of computer slide presentations to lessons. Detail the most common technological and conceptual errors: the use of photographic images of low resolution, "distortion" of the image on the slide, abuse banal images, the image on the slide, not "correlated" with the educational context. Methodical recommendations to address the negative impact of technological and conceptual errors in the visual perception of the slide.
Keywords: presentation; slide; images